(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2020)
The nexus between conflict management and organizational effectiveness in manufacturing companies in Rivers state was analyzed critically in this study. The study used a cross sectional survey-a form of quasi experimental design. The study surveyed a total of 139 workers from 12 randomly chosen companies. The research employed a systematic sampling method and drew a cumulative sample of 103 workers from the workforce. The study’s main data collection instrument was a well-structured questionnaire. The data were analyzed using the Spearman rank order correlation coefficient. The study showed a substantial link between the elements of conflict management (compromising and accommodating) and organizational effectiveness metrics (adaptability and job satisfaction). Thus, it was concluded that a well-managed conflict policy within the company would contribute to the firm’s increased effectiveness. As such, the study suggested, among other recommendations, that management of manufacturing companies employ a compromising approach when they face the possibility of losing something important, such as a highly skilled employee, as this would further maximize the firm’s rate of effectiveness.